2020
DOI: 10.21077/ijf.2020.67.4.100172-20
|View full text |Cite
|
Sign up to set email alerts
|

Potential of black soldier fly (Hermetia illucens) as alternative protein source in salmonid feeds - A review

Abstract: The current constant pressure on fishmeal production for aquaculture feeds stresses the need to search for alternative sources of protein. A possible protein ingredient is insect meal, being more cost effective than fishmeal and soybean meal. Black soldier fly (Hermetia illucens) larvae meal is used in many studies with positive results regarding the bioproductive performances of salmonids. The balanced amino acid profile is comparable with the one of soybean meal. The crude protein and amino acid digestibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Previous reviews showed that different fish species responded differently to dietary BSF 19,29 . In accordance, the present study also showed that the type of salmonid species was partially responsible for the heterogeneity of growth rate in salmonids between the studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous reviews showed that different fish species responded differently to dietary BSF 19,29 . In accordance, the present study also showed that the type of salmonid species was partially responsible for the heterogeneity of growth rate in salmonids between the studies.…”
Section: Discussionsupporting
confidence: 89%
“…The results of these two studies further emphasized that the analysis of individual insect and aquatic species can be more meaningful than the generalized results across different insect and aquatic species. The previous reviews on the topic of the effects of the use of BSF in salmonid diets concentrated on summarizing scientific literature in a narrative and qualitative approach 16,19 …”
Section: Introductionmentioning
confidence: 99%
“…The significant difference observed between BSFM and SPCM in terms of lipid ADCs may be attributed to limitations in calculation methods, especially for ingredients with low lipid content, as seen in SPCM (Table 2). While these findings are encouraging for aquafeed formulators considering the incorporation of these materials into barramundi feed, it is important to acknowledge that the nutritional quality and chemical composition of BSFM can significantly vary depending on the insect feeding media [47], between products and batches [13], and potentially with different processing methods. Therefore, further trials using diverse sources of BSFM are crucial to gain comprehensive insights into its inclusion in barramundi diets.…”
Section: Discussionmentioning
confidence: 93%
“…The BSF larvae contain antimicrobial peptides like defensins, cecropins, atacins, and diptericins (Müller et al, 2017). Therefore, larval extracts have degraded bacterial biofilms produced by Escherichia coli, Micrococcus luteus, Pseudomonas fluorescens, and Bacillus subtilis (Papuc et al, 2020). In the last decades, antibiotic resistance has been a topic of interest due to microbial resistance against antibiotics.…”
Section: Black Soldier Fly (Hermetia Illucens)mentioning
confidence: 99%